PERANCANGAN SISTEM INFORMASI GEREJA HKBP CENDANA NAULI RESORT TANJUNG MORAWA KOTA BERBASIS WEB - Sitindaon, Ester; Siringoringo, Rimbun; Harianja, Eva Julia G. (Universitas Methodist Indonesia, 2024)
The increasingly advanced development of information technology can be utilized in almost every aspect of life. It is hoped that the very rapid progress of information technology can support the tasks of an organization so that the activities carried out can be well coordinated. This also had an impact on the church to introduce a web-based church information system to the church congregation. As the first indication that an information system can be built at the Huria Kristen Batak Protestant Church (HKBP) Cendana Nauli Resort Tanjung Morawa City, this information system will be used to facilitate the collection of congregation data and church information. Based on the problems above, an information system was built that can assist in web-based data collection on church congregations. Where the website can be accessed anywhere and at any time so it does not specify time and place limits. The information system that has been built uses the PHP language. This website also provides congregation services to view worship schedules, church profiles, and photo galleries of church activities, which can be accessed easily. . By building this information system, it can help the congregation and leaders of the HKBP Cendana Nauli Resort Tanjung Morawa City parhalado more easily, quickly and efficiently in accessing church congregation data collection information and church information.